'We Don't want it to be like that for her again': gendered leadership and online feminism in Australian politics and planning. Issue 1 (2nd January 2017) - McLean, Jessica; Maalsen, Sophia
ABSTRACT: Learning from women leaders in Australia has gained attention as a national political issue since the election of Julia Gillard as our first female Prime Minister in 2010. In parallel with her period in office, a growth in feminist action and practice has been evident, in institutions and interventions such as 'Destroy the Joint', a group that agitates for an end to sexism and misogyny in multiple spaces. This article examines shifts in gendered leadership and activism, in online and offline spaces, especially with respect to learning from women's experiences in leadership, and we consider the implications of gendered politicking on planning issues. Drawing on empirical quantitative and qualitative data from an online survey of nearly 900 Destroy the Joint participants, this article looks at some impacts of national female leadership on Australian governance and what people believe should happen to achieve gender equality, in planning and political representation contexts. We argue that discourses of power and gender produced a challenging governance context for Gillard that undermined her leadership achievements but that this sexism also helped inspire growing and active feminist spaces that seek gender equality.